Gender differences in correlation of biochemical parameters with the severity of COVID pneumonia and the need for oxygen/mechanical support: Gender differences in biochemical parameters in COVID pneumonia - Janković, Jelena; Stjepanovic, Mihailo; Maric, Nikola; Belic, Slobodan (Journal of Medical Biochemistry, 2024)
Background:COVID-19 pandemic had caused a global medical, economic and social problems. High infection rate, heterogenous presentation, lack of previous data and no standardized treatment had led to a need for further analysis, in order to be prepared for any potential new pandemics. We analyzed any possible correlation between gender, laboratory findings and severity of disease with need for oxygen or mechanical ventilation support. Methods: 100 patients with confirmed SARS-CoV-2 virus infection enrolled. Baseline characteristics that included age, sex, smoking history, BMI, oxygen therapy or mechanical ventilation support need were recorded. Type and severity of radiological finding determined by chest CT scan. Results: Majority of our patients were over 61 years old (58.6%), male (57.6%), and had severe radiological finding (bilateral pneumonia 29.3%, ARDS 35.4%), with only 20.2% had not required any oxygen supplementation. Regarding gender and laboratory findings, men have shown statistically significant higher values of CRP, lymphocytes, LDH and ferritin (96.4 vs 87.1, p=0.014; 1.17 vs 0.84, p=0.048; 674.8 vs 609.1, p=0.031; 1263 vs 578.4, p=0.001, respectfully). Severe radiological finding had shown positive correlation with the need for HFNC and/or (N)IMV (p=0.021 and p=0.032. respectfully), as well as with higher values of WBC, LDH and ferritin (p=0.042, p=0.035 and p=0.017. respectfully). Conclusions: There is a difference between presentation of the disease, as well as analyzed laboratory markers between sexes. The difference is most likely multifactorial and should require further research in order to discover other risk and prognostic factors.